Pomen afriških palic na primerih iz zbirke Slovenskega etnografskega muzeja - Frelih, Marko (Etnolog. Nova vrsta (Ljubljana), 2013)
The article presents five to date unpublished staffs from the African Collection of the Slovene Ethnographic Museum. Its main focus is on the ritualstaffs of the Dogon from Mali. The article describes the phenomenon and development of staffs from ancient Egypt, Mesopotamia, Etruria, and Greece to Early Christian Ireland, and the intercultural connections with the staffs from the African Collection of the Slovene Ethnographic Museum. The research was carried out on the basis of records, iconography, and archaeological finds. The study of such staffs is important because they had a social and religious role in ancient cultures, in some places in Africa even to the present day, while they have become forgotten in Europe, with the exception oftheir use in Christian rituals and the coronation of monarchs.
Keywords: ethnology; etnologija; muzejske zbirke; obredne palice; Africa; Afrika; Mali; Dogoni; zgodovinski pregledi; Slovenski etnografski muzej